Assessing antibody stability in filter paper-preserved blood samples for wildlife disease surveillance in tropical forests - María Fernanda Menajovsky; Gabriela M. Ulloa; Julia E. Fa; Daniel Montes; Stephan Funk; Pedro Mayor (Research in Veterinary Science, 2026)

Role of funders in embedding tests in conservation practice - Rebecca K. Smith; Nancy Ockendon; Nida Al‐Fulaij; Alessandro Badalotti; Rachel Beattie; James Byrne; Sophia Cooke; Tiago de Zoeten; Winifred F. Frick; Stephan M. Funk; Douglas Gibbs; Lauren Gupta; et al. (Conservation Biology, 2026)
Effective conservation practice requires decisions based on reliable and relevant evidence, but significant gaps in the evidence base exist. Incorporating well‐designed tests of the effectiveness of interventions for biodiversity in conservation projects is one of the best ways to scale up the rate of evidence generation. Funders of conservation projects are uniquely positioned to support and incentivize such tests as part of the grant‐making process. Using a structured process, as 25 conservation funders and members of Conservation Evidence, we identified means of improving the effectiveness of the work funded through the support of enhanced evidence generation. We identified 11 approaches through which funders can support embedding testing, ranging from encouraging inclusion of a test in the project proposal, to designating separate funds for incorporating a test, to supporting an external testing unit to provide training and advice. The appropriate approaches vary depending on the scale, process, and type of funding. Barriers to supporting testing and potential solutions were discussed, barriers such as a lack of skills to check tests are appropriate and well designed and the additional time needed to develop, implement, and see outcomes of tests and differing types of projects. By encouraging testing of actions as part of conservation practice (where appropriate), funders will ultimately facilitate a stronger evidence base for more effective decision‐making and better outcomes for nature and society.

Meeting the Aichi targets: Pushing for zero extinction conservation - Stephan M. Funk; Dalia Conde; John Lamoreux; Julia E. Fa (Ambio, 2017)
Effective protection of the ~19 000 IUCN-listed threatened species has never been more pressing. Ensuring the survival of the most vulnerable and irreplaceable taxa and places, such as those identified by the Alliance for Zero Extinction (AZE) species and their associated sites (AZEs&s), is an excellent opportunity to achieve the Aichi 2020 Targets T11 (protected areas) and T12 (preventing species extinctions). AZE taxa have small, single-site populations that are especially vulnerable to human-induced extinctions, particularly for the many amphibians. We show that AZEs&s can be protected feasibly and cost-effectively, but action is urgent. We argue that the Alliance, whose initial main aim was to identify AZEs&s, must be followed up by a second-generation initiative that directs and co-ordinates AZE conservation activities on the ground. The prominent role of zoos, conservation NGOs, and governmental institutions provides a combination of all-encompassing knowhow that can, if properly steered, maximize the long-term survival of AZEs&s.

Translocation retains genetic diversity of a threatened endemic reptile in Mauritius - Sozos Michaelides; Nik Cole; Stephan M. Funk (Conservation Genetics, 2015)

The importance of cultural knowledge and scale for analysing internet search data as a proxy for public interest toward the environment - Stephan M. Funk; Daniela Rusowsky (Biodiversity and Conservation, 2014)

Investigations into the status of a new taxon of Salanoia (Mammalia: Carnivora: Eupleridae) from the marshes of Lac Alaotra, Madagascar - Joanna Durbin; Stephan M. Funk; Frank Hawkins; Daphne M. Hills; Paulina D. Jenkins; Clive B. Moncrieff; Fidimalala Bruno Ralainasolo (Systematics and Biodiversity, 2010)

First records of Trichodectes canis (Insecta: Phthiraptera: Trichodectidae) from Darwin’s fox, Pseudalopex fulvipes (Mammalia: Carnivora: Canidae) - Daniel González-Acuña; Cristóbal Briceño; Armando Cicchino; Stephan M. Funk; Jaime Jiménez (European Journal of Wildlife Research, 2007)

Ecological factors influence population genetic structure of European grey wolves - MALGORZATA PILOT; WLODZIMIERZ JEDRZEJEWSKI; WOJCIECH BRANICKI; VADIM E. SIDOROVICH; BOGUMILA JEDRZEJEWSKA; KRYSTYNA STACHURA; STEPHAN M. FUNK (Molecular Ecology, 2006)
Although the mechanisms controlling gene flow among populations are particularly important for evolutionary processes, they are still poorly understood, especially in the case of large carnivoran mammals with extensive continuous distributions. We studied the question of factors affecting population genetic structure in the grey wolf, Canis lupus , one of the most mobile terrestrial carnivores. We analysed variability in mitochondrial DNA and 14 microsatellite loci for a sample of 643 individuals from 59 localities representing most of the continuous wolf range in Eastern Europe. We tested an array of geographical, historical and ecological factors to check whether they may explain genetic differentiation among local wolf populations. We showed that wolf populations in Eastern Europe displayed nonrandom spatial genetic structure in the absence of obvious physical barriers to movement. Neither topographic barriers nor past fragmentation could explain spatial genetic structure. However, we found that the genetic differentiation among local populations was correlated with climate, habitat types, and wolf diet composition. This result shows that ecological processes may strongly influence the amount of gene flow among populations. We suggest natal‐habitat‐biased dispersal as an underlying mechanism linking population ecology with population genetic structure.

Phylogeography of the endemic St. Lucia whiptail lizard Cnemidophorus vanzoi: Conservation genetics at the species boundary - Stephan M. Funk; Julia E. Fa (Conservation Genetics, 2006)

The effect of the last glacial age on speciation and population genetic structure of the endangered Ethiopian wolf ( Canis simensis ) - DADA GOTTELLI; JORGELINA MARINO; CLAUDIO SILLERO‐ZUBIRI; STEPHAN M. FUNK (Molecular Ecology, 2004)
During the last glacial age, Afro‐alpine habitats were widespread across the highlands of Ethiopia. A wolf‐like canid ancestor is thought to have colonized this expanding habitat and given rise to a new species that was remarkably well adapted to the high altitude environment: the Ethiopian wolf Canis simensis . Here, we address the timing of genetic divergence and examine population genetic history and structure by investigating the distribution of mitochondrial DNA (mtDNA) sequence variation. The pattern of mtDNA variation and geographical distribution indicate an initial population expansion, probably immediately after divergence from the wolf‐like ancestor, around 100 000 years ago. The partition of mtDNA haplotypes that followed was most likely the result of habitat reduction and fragmentation at the onset of deglaciation ~ 15 000 years ago. Phylogenetic and geographical associations suggest that the most likely genetic partitioning corresponds to three mountain areas, Arsi/Bale, Wollo/Shoa and Simien/Mt. Guna. Although there is a degree of clustering of haplotypes from both sides of the Rift Valley, the lack of reciprocal monophyly does not support the taxonomic classification of two subspecies. This study highlights the importance of populations north of the Rift Valley for the maintenance of genetic variability within the species and has consequent implications for conservation.

Behavioural structuring of relatedness in the spotted hyena ( Crocuta crocuta ) suggests direct fitness benefits of clan‐level cooperation - Russell C. Van Horn; Anne L. Engh; Kim T. Scribner; Stephan M. Funk; Kay E. Holekamp (Molecular Ecology, 2004)
Spotted hyenas ( Crocuta crocuta ) are gregarious carnivores that live in multigenerational social groups, called clans, containing one to several matrilines. Members of multiple matrilines within a clan cooperate during dangerous interactions with inter‐ and intraspecific competitors. The evolution of cooperation may be influenced by relatedness between individuals, which in turn is influenced by reproductive skew and mate choice, dispersal and territorial behaviours. Behavioural data exist for spotted hyenas, but corresponding data on patterns of relatedness are unavailable; this lack of data makes it difficult to assess the relative importance of selection pressures favouring cooperative behaviour within and among groups. Therefore we conducted a longitudinal analysis of relatedness within a single large clan of spotted hyenas, as well as a cross‐sectional analysis of relatedness among hyenas from multiple clans. Within a clan, patterns of relatedness reflected known pedigree relationships, and relatedness was higher within than among matrilines, even across generations. Although mean within‐matriline relatedness varied among matrilines, it did not decline with matriline rank. On average, clan members were not related closely, due to high levels of male‐mediated gene flow among clans, and relatedness declined very slightly across clan borders. Low mean relatedness within clans suggests that spotted hyenas cooperate with unrelated clan‐mates against close paternal kin in other clans. Our data also suggest that spotted hyenas must derive large net direct fitness benefits from group living and cooperation.

Mitochondrial DNA Variability in Italian and East European Wolves: Detecting the Consequences of Small Population Size and Hybridization - Ettore Randi; Vittorio Lucchini; Mads Fjeldsø Christensen; Nadia Mucci; Stephan M. Funk; Gaudenz Dolf; Volker Loeschcke (Conservation Biology, 2000)
The Italian wolf ( Canis lupus ) population has declined continuously over the last few centuries and become isolated as a result of the extermination of other populations in central Europe and the Alps during the nineteenth century. In the 1970s, approximately 100 wolves survived in 10 isolated areas in the central and southern Italian Apennines. Loss of genetic variability, as suggested by preliminary studies of mitochondrial DNA (mtDNA) sequences, hybridization with feral dogs, and the illegal release of captive, non‐native wolves are considered potential threats to the viability of the Italian wolf population. We sequenced 546 base pairs of the mtDNA control region in a comprehensive set of Italian wolves and compared them to those of dogs and other wolf populations from Europe and the Near East. Our data confirm the absence of mtDNA variability in Italian wolves: all 101 individuals sampled across their distribution in Italy had the same, unique haplotype, whereas seven haplotypes were found in only 26 wolves from an outbred population in Bulgaria. Most haplotypes were specific either to wolves or dogs, but some east European wolves shared haplotypes with dogs, indicative of hybridization. In contrast, neither hybridization with dogs nor introgression of non‐native wolves was detected in the Italian population. These findings exclude the introgression of dog genes via matings between male wolves and female dogs, the most likely direction of hybridization. The observed mtDNA monomorphism is the possible outcome of random drift in the declining and isolated Italian wolf population, which probably existed at low effective population size during the last 100–150 years. Low effective population size and the continued loss of genetic variability might be a major threat to the long‐term viability of Italian wolves. A controlled demographic increase, leading to recolonization of the historical wolf range in Italy, should be enforced.